Critical Comparison Between Modified Monier-Williams and Electrochemical Methods to Determine Sulfite in Aqueous Solutions - Aguirre-Quintana, M; Aguirre-Quintana, M; Velez-Cifuentes, J; Arce-Escobar, R; Arce-Escobar, R (2012)
In the present work, known concentration of sulfite aqueous solutions in the presence and absence of gallic acid was measured to corroborate the validity of modified Monier-Williams method. Free and bound-sulfite was estimated by differential pulse voltammetry. To our surprise, the modified Monier-Williams method (also known as aspiration method) showed to be very inaccurate for free-sulfite, although suitable for bound-sulfite determination. The differential pulse approach, using the standard addition method and a correction coefficient, proved to be swift, cheap, and very precise and accurate. © Copyright 2012 C. Montes et al.